2019
DOI: 10.1111/jpc.14481
|View full text |Cite
|
Sign up to set email alerts
|

Association of maternal vitamin D deficiency and infants' neurodevelopmental status: A cohort study on vitamin D and its impact during pregnancy and childhood in Indonesia

Abstract: Aim: Vitamin D deficiency in early pregnancy may cause the disruption of fetal brain development and neurodevelopmental function. This study aimed to explore the extent of neurodevelopment disruption could be associated with maternal vitamin D deficiency. Methods: A cohort study was conducted in Sukabumi and Waled, West Java, Indonesia, beginning in July 2016. Maternal serum 25(OH)-vitamin D was measured between 10 and 14 weeks of gestational age. Child development was measured using the Ages and Stages Questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 15 publications
1
22
1
Order By: Relevance
“…5 A previous study on vitamin D level in the first trimester of pregnancy, which is a part of this cohort study, showed that the mean value of maternal 25 (OH) vitamin D level was 17.52 ng/mL. 7 This result is similar to other previous studies 6,8 which showed that newborn vitamin D level is lower (75-90%) than maternal vitamin D level. This could happen because the mother had to fulfill her own vitamin D requirement beside her fetal.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…5 A previous study on vitamin D level in the first trimester of pregnancy, which is a part of this cohort study, showed that the mean value of maternal 25 (OH) vitamin D level was 17.52 ng/mL. 7 This result is similar to other previous studies 6,8 which showed that newborn vitamin D level is lower (75-90%) than maternal vitamin D level. This could happen because the mother had to fulfill her own vitamin D requirement beside her fetal.…”
Section: Discussionsupporting
confidence: 84%
“…6 This study, as a part of the first cohort study in Indonesia about Vitamin D status and its impact on pregnancy and childhood in Indonesia. 7 amygdala and hippocampus areas. 14,15 Calcitriol also works by affecting the production of cytokines and affecting neurotransmitters and synaptic plasticity, which play important roles in the learning process and neurocognitive development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vitamin D therefore appears to play an important role in several child neurodevelopment issues and to have certain neuroprotective factors. However, few studies have focused on these topics and their findings are not conclusive [ 10 , 11 , 12 ]. Two recent systematic reviews concluded that low prenatal vitamin D status was associated with adverse infant neurodevelopment in cognitive, language, and motor skills [ 5 , 13 ] (Janbek, Specht, and Heitmann, 2019; Villalobos, Tous, Canals, and Arija, 2019).…”
Section: Introductionmentioning
confidence: 99%